Are patients' and doctors' accounts of the first specialist consultation for chronic back pain in agreement? - White KB; Lee J; Williams AC (Journal of Pain Research, 2016)
Kathy B White,1 John Lee,2 Amanda C de C Williams3 1Central and North West London NHS Foundation Trust, 2School of Life and Medical Sciences, University College London, 3Research Department of Clinical, Educational and Health Psychology, Faculty of Brain Sciences, University College London, London, UK Introduction: The first consultation at a specialist pain clinic is potentially a pivotal event in a patient’s pain history, affecting treatment adherence and engagement with longer term self-management. What doctors communicate to patients about their chronic pain and how patients interpret doctors’ messages and explanations in pain consultations are under-investigated, particularly in specialist care. Yet, patients value personalized information about their pain problem.Patients and methods: Sixteen patients in their first specialist pain clinic consultation and the doctors they consulted were interviewed shortly after the consultation. Framework analysis, using patient themes, was used to identify full match, partial match, or mismatch of patient–doctor dyads’ understandings of the consultation messages.Results: Patients and doctors agreed, mainly implicitly, that medical treatment aiming at pain relief was primary and little time was devoted to discussion of self-management. Clinically relevant areas of mismatch included the explanation of pain, the likelihood of medical treatments providing relief, the long-term treatment plan, and the extent to which patients were expected to be active in achieving treatment goals.Discussion: Overall, there appears to be reasonable concordance between doctors and patients, and patients were generally satisfied with their first consultation with a specialist. Two topics showed substantial mismatch, the estimated likely outcome of the next planned intervention and, assuming (as doctors but not patients did) that this was unsuccessful, the long-term treatment plan. It appeared that more complex issues often generate divergence of understanding or agreement. Despite the widespread recommendations to medical practitioners to check patients’ understanding directly, it does not appear to be routine practice. Conclusion: It is hoped that this research encourages more detailed examination of shared and divergent experiences of pain consultations and also their influence on the subsequent course of intervention and adherence to treatment (not addressed here). Keywords: doctor–patient communication, pain clinic, patient information, biopsychosocial, rehabilitation